1951
DOI: 10.1136/hrt.13.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Gangrene in Myocardial Infarction

Abstract: Peripheral gangrene caused by the extreme vaso-constriction that accompanies severe circulatory failure in such a disease as cholera is well recognized. Its occurrence, however, as a complication of myocardial infarction is such an uncommon event, to judge from the literature, that the reporting of two cases seems to be justified. On admission he was severely dyspnoeic at rest. There was no cedema. He was pale and it was noted that the end of his nose was blue and cold. The pulse was impalpable at the wrist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1951
1951
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Symmetrical peripheral gangrene is described as multiple extremity ischemia at two or more sites in the absence of large vessel obstruction [1,2]. Possible etiological factors cited in literature include obstructive intracardiac lesions [3], sepsis [4], vasospastic conditions [5,6], small vessel obstruction [1], protein C deficiency [7], use of vasopressor agents [8,9], low cardiac output states [10,11], disseminated intravascular coagulation (DIC) [12,13], factor V Leiden mutation [14], and parenteral abuse of the sublingually available form of buprenorphine [15]. It is well established that the digital perfusion will drop to zero in presence of persistently low perfusion pressures of 35-60 mmHg [16].…”
Section: Discussionmentioning
confidence: 99%
“…Symmetrical peripheral gangrene is described as multiple extremity ischemia at two or more sites in the absence of large vessel obstruction [1,2]. Possible etiological factors cited in literature include obstructive intracardiac lesions [3], sepsis [4], vasospastic conditions [5,6], small vessel obstruction [1], protein C deficiency [7], use of vasopressor agents [8,9], low cardiac output states [10,11], disseminated intravascular coagulation (DIC) [12,13], factor V Leiden mutation [14], and parenteral abuse of the sublingually available form of buprenorphine [15]. It is well established that the digital perfusion will drop to zero in presence of persistently low perfusion pressures of 35-60 mmHg [16].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral vasoconstriction has been held to be responsible for referred cardiac pain by Roberts (1945) and has been demonstrated by variations of cutaneous temperature (Doret and Ferrero, 1951). An analogous mechanism is known to be responsible for the trophic lesions in the upper limb which are well-recognized clinical sequelae of acute cardiac pain and myocardial infarction (Askey, 1941;Kehl, 1943;Johnson, 1943;Steinbrocker, Spitzer, and Friedman, 1948;Hilker, 1949;Chitwood, 1950;Swan and Henderson, 1951). Apart from possibly initiating reflexes, which may cause spasm of the peripheral vessels, the coronary arteries themselves are subject to vasospastic stimuli from various organs of the body (von Bergmann, 1932;Greene, 1935;Gilbert, Fenn, and LeRoy, 1940;Freedberg, Spiegi, and Riseman, 1944).…”
Section: Discussionmentioning
confidence: 99%
“…The place and nature of these reactions in the complex picture of acute left ventricular failure still remain to be clarified. We can all observe from time to time in the dying patient with left ventricular failure an intense peripheral constriction which may lead to actual gangrene of the tip of the nose and fingers (Swan and Henderson, 1951). lIn one such patient Dr. Graham Bull (unpublished) demonstrated that there was also a very gross reduction of renal blood flow to less than one-tenth the normal value.…”
Section: The Present Positionmentioning
confidence: 96%